Cultural Policy in European Context - Pârvu, Oana (Calitatea Vieții, 2014)
Culture is a component of the identity of a society, is a factor of social cohesion and through its cathartic and adaptive function, it is inextricably linked to the quality of life. Cultural policies in Europe focus on encouraging cultural diversity and intercultural dialogue, improving knowledge and dissemination of culture, conservation and protection of cultural heritage, preservation of artistic creations, culture being an important element in the development of relations between the EU Member States. “Creative Europe” is a program of the European Commission, constituted and implemented in order to support cultural and media sectors. The duration of the program is between 2014 and 2020. The main objectives of this program are encouraging cooperation between cultural organizations from different EU countries, supporting literary translations in other languages, facilitating the access for all European citizens to cultural products, creating platforms for the development of relations between artists of different countries, in order to stimulate the development and implementation of new cultural programs. In Romania, the sectoral strategy in the field of culture and national heritage for 2014–2020 was created according to European cultural policy objectives. In developing this strategy, a particular attention was directed toward youth and cultural policy. In this context, the main objectives are: to increase youth access and participation in cultural life and promoting better access of youth to jobs in the cultural field.